ANALISIS EFEKTIVITAS DAN KONTRIBUSI SUB SEKTOR PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA JAMBI - Adinda Sartika; Rosmeli; Putri Intan Suri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness and contribution of each regional tax sub-sector to the Regional Original Income (PAD) of Jambi City during the 2011–2024 period. The research method used is library research with secondary data sourced from the Regional Government Financial Report (LKPD) and the Budget Realization Report (LRA) of the Regional Tax and Retribution Management Agency (BPPRD) of Jambi City. Data analysis was carried out using effectiveness analysis by comparing tax realization against the set targets, as well as contribution analysis by comparing the realization of each tax to the total PAD realization. The results show that Land and Building Acquisition Fee (BPHTB) and PPJ have the highest level of effectiveness and contribution among all regional tax sub-sectors. Conversely, Groundwater Tax has the lowest level of effectiveness and contribution. Street Lighting Tax also shows a significant contribution to PAD. Overall, regional taxes play an important role in supporting PAD growth, but optimization efforts in several sub-sectors are still needed to improve the fiscal independence of Jambi City.